Value of Maxillary Sinus Morphology in Identification of Gender by Using Digital Radiography - Younas Khan, Sadia Syed, Riffat Shamim, Syeda Bano, Shabir Ahmed Orakazai, Zafar Iqbal (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Human being recognition is significant for a variety of purposes, including for the humanitarian and sentimental needs for others, for relatives as well as for the court before rendering a decision. In forensic radiology, the radiographic tests and procedures that are relevant to the law or the courts are performed, interpreted, and then reported. Comparing radiography to three-dimensional (3D) cone beam computed tomography, radiography has the benefits of being more widely available, having a lower radiation dose, and having a lower cast. The systemic change in size or shape between individuals of varying sexes belonging to the same species is known as sexual dimorphism. Sexual dimorphism is reflected by different species’ maxillary sinuses. The first paranasal sinus to develop in utero at the age of 10 weeks are the maxillary sinuses, which are two air-filled cavities found in the maxillary bone. They are the largest of the paranasal sinuses. Bones like the pelvis, skull, and femur are used in radiology to identify gender. Maxillary sinuses can be utilized for identification in mass tragedies like aero plane accidents, war, explosions, burnt, decomposing remains, and other calamities. In these situations, all the bones suffer severe damage, but the sinuses are left undamaged. Aim and objective: This research used digital radiography to identify gender based on the morphology of the maxillary sinus. Materials and Methods: From the radiographs (A.P view) of 128 subjects ( 64 males and 64 females), the morphometric characteristics of the maxillary sinus were assessed using microdicom software. Results: The right maxillary sinus average height and width in males was 28.15mm and 25.04mm whereas, in females it 22.39mm and 22.54mm respectively and was found statistically highly significant. Likewise, the left maxillary sinus average height and width in males was 28.91mm and 25.33mm and in females it was 22.39mm and 20.81mm respectively and was statistically highly significant. Conclusion: It was concluded from my study that the anteroposterior (AP) view of digital radiographs can be used to detect the gender based on the height and width of the maxillary sinuses. Keywords: Forensic radiography, maxillary sinus, sexual dimorphism, gender determination mass disaster.